COMPARISON ANALYSIS BETWEEN MALE AND FEMALE OF CONSUMER PURCHASE BEHAVIOR OF YAMAHA MIO - Pakasi, Alfa; Tumiwa, Johan (Universitas Sam Ratulangi, 2016)
Humans have many needs and wants that they must fulfill in his life. Motorcycles is one requirement that must be met to be used as a means of transportation. Male and female have their own criteria for selecting the type of motorcycle they want. Male and female have different decision-making to buy a motorcycle. The method used in this research is the method of comparative data, collecting data through questionnaires, data analysis methods (validity and reliability), hypothesis testing and independent sample t-test. The results showed a significant difference between male and female in the purchasing behavior of consumers towards Yamaha Mio. Yamaha Mio sellers should consider offering their products for men and women differently. Keywords: decision making, consumer purchase behavior